Первобытный человек - Нейман Марина (Энциклопедия Знатока, 2006)
Экземпляры: ф-23 (ретроконверсия) / Инвентарный номер: 41830 / Цена: 132.00 / Сис.шифр: 63.3(0)2 / Авт.знак: П 26 / ГРНТИ: 03 / ББК: 63.3(0)2